Current status and challenges in timely detection of cervical cancer in Mexico: expert consensus - Barquet-Muñoz, Salim Abraham; Arteaga-Gómez, Cristina; Díaz-López, Elsa; Rodríguez-Trejo, Amelia; Marquez-Acosta, Janeth; Aranda-Flores, Carlos (Frontiers in Oncology, 2024)
Cervical cancer remains a significant public health concern in low-and middle-income countries, accounting for a substantial proportion of new cancer cases and deaths worldwide. In poorly organized screening programs, vulnerable populations who do not participate or receive regular screening are at an increased risk of developing cervical cancer. The recommended screening tools for cervical cancer, supported by scientific evidence for routine use, include cervical cytology and testing for high-risk human papillomavirus (HPV). Additionally, various strategies have been explored to utilize these tools effectively to identify women at higher risk of cervical cancer and extend the intervals between negative screening tests with greater confidence. Ongoing research is evaluating innovative early detection methods, such as selfsampling for vaginal or urinary HPV testing, with the potential to improve screening coverage.Furthermore, studies investigate biomarkers that can enhance detection accuracy and provide more precise results. This consensus chapter aims to address the challenges associated with early detection programs and screening tools for cervical cancer in Mexico. It provides evidence-based recommendations to strengthen and improve early detection efforts, ultimately leading to better outcomes and a reduction in the burden of cervical cancer in the country.